PENGEMBANGAN PENGINTEGRASIAN PENDIDIKAN LALU LINTAS DALAM MATA PELAJARAN PKN MELALUI MEDIA PEMBELAJARAN BERBASIS WEB UNTUK MENINGKATKAN KESADARAN HUKUM PESERTA DIDIK DI SMPN 5 BANDUNG - Rio Razab Isdendi Razab Isdendi (JURNAL BUANA INFORMATIKA CBI, 2018)
Teenage drivers are famous for unsafe and disorderly driving behavior, and a minimal level of awareness in traffic. In thiscase the researcher wants; 1) knowing the learning conditions of traffic education integration materials in Civic Educationsubjects at SMP Negeri 5 Bandung, 2) knowing how to develop web-based learning media for conceptual education of traffic education materials in Civics subjects, 3) knowing how to implement learning-based media web in conceptual integration of traffic education material in Civics subjects, 4) knowing the increase of students' legal awareness after theapplication of web-based learning model in the material of integrating traffic education in Civics subjects. Somantri (Wuryan and Syaifullah, 2009.76) interpreted Civics as a selection, adaptation from cross-disciplines of social sciences, citizenship, humanities, technology, religion, basic human activities organized and presented psychologically andscientifically. to participate in achieving one of the objectives of social science education and national education goals. The approach used by researchers is the Research and Development (R & D) approach. By using data collectiontechniques, including observation, interviews, questionnaires, literature studies, documentation studies. The population used is the population of SMPN 5 Bandung. The research samples were: class VII-A, class VII-B, class VII-C, class VII-D, and class VII-E. Analysis of his research uses qualitative analysis and quantitative analysis. The results showed that; 1) the condition of learning the integration of traffic education in Civics subjects is still conservative, especially in theuse and use of learning media, resulting in students being less interested in learning material for integrating traffic education in Civics subjects, 2) producing web-based learning media that in accordance with the purpose of its manufacture, the stages that must be carried out by the media developer are starting from the preproduction, productionand post-production stages. To be able to run this web-based learning media does not require special skills in learning, only basic computer skills are needed for teachers and students because this web-based learning media usescomputer media and internet connection, 3)web-based learning media contributes significantly to increasing legal awareness student traffic in learning material integrates traffic education in Civics subjects and 4)contributes significantly to improving student learning outcomes.